An investigation of English reading comprehension text difficulties among master level Saudi students - Sajid, Muhammad Khalid Mehmood (Globeedu Group, 2018)
The purpose of this research was to explore the English reading comprehension text difficulties among master level Saudi students to support the reading comprehension of students with reading difficulties. The literature is mixed in regard to the different difficulties students have in reading comprehension. The Research examined the specific problems faced by these students in the literature. A survey study was conducted. 120 master level students were the participants, with reading difficulties who participated in this study. Convenience sampling was used. The findings showed that the highest difficulties faced by Saudi students on reading comprehension text were vocabulary, reading speed and the less difficult problems faced by Saudi students on reading comprehension text was reading aloud by the students. However, it was recommended that the publishers should introduce supplements or bilingual glossaries, and there should be matching text with the learning material. Further, any planned reading aloud by the instructors for these master level students can produce good text comprehension. Nevertheless; linguistics and lexical knowledge were also recommended for these master level students.